A Philosophical Analysis of Jacques Derrida’s Contributions to Language and Meaning - John Gabriel Mendie; Stephen Nwanaokuo Udofia (Universitas Negeri Makassar, 2021)
Far from being a banality or a philosophical naivety, there is a quintessential nexus between language and meaning, in the philosophy of Jacques Derrida (1930-2004). The thrust of Derrida’s idea is that, language is chaotic and meaning is never fixed, in a way that allows us to effectively determine it (that is, meaning is unstable, undecided, provisional and ever differed). As a Poststructuralist, Derrida’s quarrel was with Logocentrism, which privileges speech over writing, and hitherto assume that, we have an idea in our minds, which our writing or speaking attempts to express. But, this, for Derrida, is not the case, for no one possesses the full significance of their words. Texts, in some sense write themselves: that is, are independent of an author or his intentions. Thus, in Derrida’s thinking, intentionality does not play quite the same role, as is traditionally conceived in the philosophy of language; our intention does not determine the meaning of what we are saying. Instead, the meaning of the words we use, determines our intention, when we speak. This does not mean that we do not mean what we are saying, or that we cannot have intentions in communicating. But, since language is a social structure that developed long before and exists prior to our use of it as individuals, we have to learn to use it and tap into its web of meanings, in order to communicate with others; hence, the need for deconstruction. It is this process of deconstruction, which can point the way to an understanding of language, freed from all forms of structuralism, logocentrism, phonocentrism, phallogocentrism, the myth or metaphysics of presence and also open up a leeway, to the idea of différance. Thus, this paper, attempts an expository-philosophical analysis of Derrida’s eclectic contributions to language and meaning, by drawing insights from his magnus opus, captioned De la grammatologie (Of Grammatology).